The Problem of Illicit Gold Mining from The Standpoint of a State Upholding The Rule of Law - Tries Edy Wahyono; Mochtar, Mochammad; Soediono, Ricardo; Emilia; Romli, Mustain (International Journal of Sustainable Law, 2024)
The three primary questions this research seeks to address are: How does criminal law approach environmental issues, such the PETI case, and what are the ethical philosophy of preventative initiatives' perspectives on solving environmental issues? as well as the measures taken by the government to address this issue. This paper uses a qualitative research methodology that is somewhat juridical-empirical in character. Written resources (books, journals, papers, etc.) are the source of data for this topic. This research study divides textual material into two categories: main and secondary. Criminal threats, such as jail time and fines, must exist for PETI offenders, as mentioned in the articles. Further criminal or disciplinary penalties under Article 119 Law Number 32 of 2009 concerning Environmental Protection and Management can be imposed on commercial companies. People need to understand their own roles, obligations, and responsibilities in life. in order for this moral idea to serve as a safeguard against human-caused environmental harm. Lastly, in regards to the government policies that also need to play a role in solving this PETI issue, these include: offering support to enable PETI to become a legal business; offering technical help; offering financial support for development; and offering access to prevent business actors from feeling pressured to legalize a business. the mining.